Exploring Students’ Difficulties on Writing English Paragraph at English Education Study Program of FKIP UKI Toraja - Ippun, Desi; Patanduk, Sushy Teko; Sirande, Normalia (Jurnal Studi Guru dan Pembelajaran, 2023)
The purpose of this study was to determine and understand the difficulties faced by students in writing English paragraphs in the English Education Study Program at FKIP UKI Toraja. In this study, the researchers used quantitative method. The researcher took data from students of UKI Toraja English Study Program in the 2023/2024 academic year. Who have passed the Writing paragraph course. The author chose 20 students majoring in English at UKI Toraja. To find out what are the difficulties faced by students of English education study program FKIP UKI TORAJA in writing English paragraphs, the researcher used questionnaire with Likert scale. Based on the results of the data analysis, overall, most students found difficulties in writing paragraphs generally positive, where the majority of students experienced difficulties in writing paragraphs especially in finding ideas (80%), limited vocabulary, and lack of confidence. In addition, 70% of respondents faced challenges in connecting ideas, as well as problems of motivation and boredom while writing. Difficulty starting sentences, maintaining the flow of writing, and concerns about grammar and clarity were also major concerns. Anxiety towards the writing task and the tendency to procrastinate indicated the need for emotional support and better time management strategies.